Pelatihan Digital Branding dan Marketplace Onboarding Berbasis Smartphone Bagi Ibu-Ibu Dharma Wanita Lldikti Wilayah 6 Semarang - Sri Sulistyowati; Devi Permatasari; Naila Najihah (Jurnal Penelitian dan Pengabdian Masyarakat, 2026)
This community service program introduced a practical training model consisting of Canva-based digital branding and Shopee marketplace onboarding, using decoupage craft products as the practice object. All activities were conducted using participants’ own smartphones, so no additional equipment was needed. The program was carried out in three stages: preparation, including a needs survey and module development; implementation, through four structured training sessions with individual mentoring; and evaluation, using pre-test and post-test scores. Twenty participants joined the program. The results showed clear improvement, with the average score increasing from 18.3 to 70.8 and a gain score of 0.65. All participants successfully created Instagram Business and WhatsApp Business accounts, while 60% uploaded their products to Shopee. Overall, this program shows that smartphone-based digital branding and marketplace training can effectively improve women’s digital marketing capacity in semi-formal organizations